Depression, insomnia and psychoactive substances consumption in nursing staff in COVID-19 area - Carreón Gutiérrez, Carlos Alberto; De los Reyes Nieto, Laura Roxana; Vázquez Treviño, María Guadalupe Esmeralda; Loredo Lárraga, Laura Virginia; Cadena Santos, Francisco; Méndez Ruíz, Martha Dalila (Horizonte Sanitario, 2025)
Abstract Objective: To evaluate the relationship between depression and insomnia and their interaction with sociodemographic, occupational, and substance use factors among nursing professionals in COVID-19 areas. Material and Methods. A sample of 222 nursing professionals residing in Tamaulipas, Mexico, who cared for COVID-19 patients during the period July-August 2022. Demographic, occupational, and substance use data were collected. The Insomnia Severity Index (ISI-7) and the Patient Health Status Assessment Questionnaire (PHQ-9) were used to assess depression levels. Variables were analyzed using descriptive statistics. The Spearman correlation coefficient and chi-square test were used for correlational analysis; and the Mann-Whitney U test and Kruskal-Wallis H test were used for comparisons between groups. Results: 79.3% of nursing professionals are female, and 33.8% work night shifts. The median age was 34 years, and their seniority was 7 years. High prevalence rates were found for alcohol (82.0%), tobacco (46.4%), and marijuana (14.9%). Fifty percent of staff presented moderate to severe depression, and 51.3% had insomnia. There is a significant association between insomnia and depression and psychotropic substance use (p<.000), with users presenting the most disturbed levels (p<.000). Depression and insomnia levels were higher in younger workers (depression: rs = –.295; insomnia: rs = –.335) and in older workers (depression: rs = –.344; insomnia: rs = –.345), with significant correlations (p < .000). The night shift was the most affected by depression (p < .05). Conclusion: Depression and insomnia were situations that nursing professionals faced during the COVID-19 pandemic, experiencing a complex adaptation process characterized by the use of alcohol, tobacco, and other substances.